EVALUASI KEBIJAKAN PEMBERDAYAAN APARATUR PEMERINTAH KELURAHAN (Suatu Studi Di Kecamatan Tahuna Barat Kabupaten Kepulauan Sangihe) - KASEALA, YULIFILA INDRA; Kiyai, Burhanuddin; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : The smoothness of the administration and national development depends on the perfectionof the state apparatus , including officials at all levels of government, from the village / village level tothe central government / national. government apparatus as a tool for implementing governmentaffairs , development, premberdayaan and publik services, it is necessary for employees / personnelwho truly capable, efficient, high quality, and be aware of his responsibility as a servant of the stateand publik servant.This study used quantitative research approaches evaluatif.Adapun types of research methodsused in this study is a survey method. In survey research, information / data collected from respondentsusing a questionnaire. Generally limited in terms of understanding the survey sample survey in whichinformation is collected from the part of the population to represent the entire population.In this study were all village officials and community spread in 6 ( six ) villages in the districtsof West Tahuna. Tahuna Western District of statistical data, the year 2013 recorded the number ofcivil servants, including village officials that there dikecamatan Tahuna West ( 6 villages ) as many as152 people. Given the large population in the category of minimal, then the respondent sample ispulled by 50 %, thus becoming 76 village officials as respondents in this study spread over threevillages sampled, namely : Pananekeng Village, Village brassiere, Village New brassiere.Keywords : Evaluation , Policies , Empowerment , Government Apparatus